Anisotropy in the mechanical properties of organic crystals: temperature dependence1. Issue 79 (28th August 2015) - Mohamed, Reda M.; Mishra, Manish Kumar; AL-Harbi, Laila M.; Al-Ghamdi, Mohammed S.; Ramamurty, Upadrasta
<x xml:space="preserve">Abstract</x> Nanoindentation technique was employed on organic molecular crystals to investigate how the anisotropy in the mechanical behavior changes within the temperature range of 283 to 343 K.